Novel platinum complexes having chirality and free tertiary amine groups for multiple interactions with DNA - Mi, SS; Sohn, YS; Yang, BS; Nam, W; Kim, KM (ELSEVIER, 2004)
Chiral ethylenediamine ligands with free tertiary amine groups and their platinum complexes are synthesized. The platinum complexes have both chirality and additional DNA interacting groups. The hydrogen bonding interactions between chlorides and two tertiary amine groups in the crystal structure lead to the dimerization of two platinum complexes having pocket-like cavity with chiral shapes. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CISPLATIN